2010
DOI: 10.1002/dvdy.22192
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sox9 by Sonic Hedgehog (Shh) is essential for patterning and formation of tracheal cartilage

Abstract: We report that Sonic Hedgehog (Shh) regulates both formation and patterning of tracheal cartilage by controlling the expression pattern and level of the chondrogenic gene, Sox9. In Shh 2/2 tracheo-esophageal tubes, Sox9 expression is transient and not restricted ventrally to the site of chondrogenesis, and is absent at the time of chondrogenesis, resulting in the failure of tracheal cartilage formation. Inhibition of Hedgehog signalling with cyclopamine in tracheal cultures prevents tracheal cartilage formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 49 publications
6
91
0
Order By: Relevance
“…We analyzed the expression of SRY (sex-determining region Y)-box 9 (SOX9), a master regulator of chondrogenesis essential for patterning and formation of the tracheal cartilage (Park et al, 2010). In E14.5 controls, the segmented SOX9 expression showed the pattern of the future cartilage rings.…”
Section: Mek1 Epithelial Inactivation On a Mek2 Null Background Resulmentioning
confidence: 99%
“…We analyzed the expression of SRY (sex-determining region Y)-box 9 (SOX9), a master regulator of chondrogenesis essential for patterning and formation of the tracheal cartilage (Park et al, 2010). In E14.5 controls, the segmented SOX9 expression showed the pattern of the future cartilage rings.…”
Section: Mek1 Epithelial Inactivation On a Mek2 Null Background Resulmentioning
confidence: 99%
“…These results show that a 50% reduction of Sox9 already leads to a lethal phenotype in humans and mice. In mice lacking sonic hedgehog, the level of Sox9 is almost absent at the time of chondrogenesis, resulting in the failure of tracheal cartilage formation (34). The reduced percentage of Sox9 in Ca v 3.2 −/− trachea (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…A certain level of Sox9 expression is essential for the condensation of chondroprogenitor cells into segments along developing trachea at E14.5 (14,34). Sox9-positive cells formed a clear banding pattern on the ventral side of developing trachea in WT but not Ca v 3.2 −/− mice (Fig.…”
Section: Ca V 32 Enhances Chondrogenesis In a Calcineurin/nfat-depenmentioning
confidence: 93%
“…6) Shh mice indicated that Shh signaling is a key determinant in cartilage development. 25) Furthermore, cyclopamine, which is a steroidal alkaloid derived from plants, can block Shh signaling by inhibition of smoothened, [26][27][28] preventing atractylenolide from positively regulating Gli promoter activity, chondrogenic markers and Sox9 expression. These results demonstrated that the effects of atractylenolide on chondrogenic differentiation in MSCs are dependent on Shh signaling.…”
Section: Discussionmentioning
confidence: 99%